Power converters for three phase electric locomotives - Suresh, H.; Vaibhav, A. M.; Suresh, H. N. (Linguistics and Culture Review, 2021)
This paper is about the simulation study of auxiliary converters used in 6000 HP electric locomotives used in India. Simulation is a mirror of the operation of a real-world method or system. The process of simulating a system first requires that a model be designed. This model represents the key behaviors, characteristics, and functions of the selected physical or abstract system. It helps to analyze the behavior of the system without even building it. The results obtained are accurate in general when compared to the analytical model. It also helps to find unexpected errors and behavior of the system. Simulation is easy to perform “What-If” analysis. For this purpose, MATLAB/Simulink was used.